Nacre microstructure records spatiotemporal variation in temperature in the modern ocean - Carskaddan, Jane S.; Rillo, Marina C.; Harnik, Paul G.; Metzler, Rebecca A. (Frontiers in Marine Science, 2025)
Changing climatic conditions can have complex effects on the biomineralized segments of marine organisms, which in turn may influence individual fitness and survival. In nacreous shells, tablet thickness is one microstructural component that has been observed to positively correlate with ocean temperature, though the strength of this relationship is unclear, leaving unresolved whether temperature is a consistent predictor of tablet thickness and, if so, over what scales. Here we investigate the relationship between tablet thickness and temperature in two nacre-producing marine mollusks in the modern ocean. We explore the relationship between nacre tablet thickness and ocean temperature through a global analysis of present-day abalone (Haliotis) nacre, and a temporal analysis of nut clam (Nucula proxima) nacre using shells from individuals that lived before and after 1950 in two regions of the Gulf of Mexico. We document a positive relationship between tablet thickness and ocean temperature within and among closely-related species. For a given temperature, considerable variation was observed in nacre tablet thickness, indicating that other factors also contribute. While increased temperature is likely to cause larger biomineralized units within the calcified segments of marine organisms, other environmental factors might counter those changes, highlighting the need for work exploring the multimodal impact of anthropogenic climate change on biominerals.